Synthesis of bioactive quinazolin-4(3H)-one derivatives via microwave activation tailored by phase-transfer catalysis - El-Badry Yaser A.; El-Hashash Mahr A.; Al-Ali Khalil (Acta Pharmaceutica)
A series of nine new 2,3-disubstituted 4(3H)-quinazolin-4-one derivatives was furnished starting from the 2-propyl-4(3H)-quinazo-line-4-one (2). The reinvestigation of the key starting quinazolinone 2 was performed under microwave irradiation (MW) and solvent-free conditions. Combination of MW and phase-transfer catalysis using tetrabutylammonium benzoate (TBAB) as a novel neutral ionic catalyst was used for carrying out N-alkylation and condensation reactions of compound 2 as a simple, efficient and eco-friendly technique. The structure of the synthesized compounds was elucidated using different spectral and chemical analyses. In vitro antimicrobial activity of the compounds was investigated against four bacterial and two fungal strains; very modest activity was achieved. Some of the synthesized compounds were screened for their antitumor activity against different human tumor cell lines. The screened compounds exhibited a significant antitumor activity on some of the cancer cell lines, melanoma (SK-MEL-2), ovarian cancer (IGROV1), renal cancer (TK-10), prostate cancer (PC-3), breast cancer (MCF7) and colon cancer (HT29). The most active, even more active than the reference 5-fluorouracil, were found to be ethyl 4-[(4-oxo-2-propylquinazolin-3(4H)-yl)methyl]benzoate (3c), 3-{2-[6-(pyrrolidin-1-yl-sulfonyl)-1,2,3,4-tetrahydroquinoline]-2-oxoethyl}-2-propylquinazolin--4(3H)-one (3e), N’-[(E)-(2H-1,3-benzodioxo-5-yl)methylidene]-2-(4-oxo-2-propylquinazolin-3(4H)-yl)acetohydrazide (10a), N’-[(E)-(4-hydroxyphenyl)methylidene]-2-(4-oxo-2-propylquinazo-lin-3(4H) -yl)acetohydrazide (10b) and N’-[(E)-(4-nitrophenyl)methyl idene]-2-(4-oxo-2-propylquinazolin-3(4H)-yl)acetohydrazide (10c).